Examining the Effectiveness of Short YouTube Videos to Escalate the Students’ Listening Comprehension - Muhammad Rizki Firman Setiawan; Dian Fadhilawati (CV. Kalimasada Group Profesional, 2023)
This pre-experimental study examined the efficacy of YouTube Shorts videos in escalating the listening comprehension of 26 elementary school students. Employing a one-group pre-test and post-test design, the research procedure encompassed pre-testing, implementing the treatments, and conducting post-tests. Data were collected through comprehensive assessments and subsequently analyzed using SPSS 26. The findings unveiled a significant improvement in the students' listening abilities, with scores surging from an initial 52.42 to an impressive 81.63. Remarkably, the two-tailed significance value (Sig2) yielded a minuscule figure of 0.000, well below the significance threshold of 0.05. This compelling outcome underscores the effectiveness of YouTube Shorts videos as a medium for elevating students' listening comprehension. As a resounding recommendation, elementary English teachers are strongly urged to incorporate YouTube Shorts videos as an innovative and impactful resource in their pedagogical journey, especially for teaching listening skills, thereby augmenting the overall learning experience and outcomes of their students.